THE VALUE OF TEACHERS’ EFFECTIVE PRAISE AND FEEDBACK TO ADULT LEARNERS TO CREATE A POSITIVE CLASSROOM CLIMATE - Henny Mardiah (UIN Sumatera Utara, 2020)
Recent studies have demonstrated that praise for academic performances can affect students’ intrinsic motivation and performances in learning. This study aims to investigate the value of teachers’ effective praise and feedback to adult learners to create a positive classroom climate. The participants of this study were 41 students of fourth semester, TBI-4, UINSU. This study was conducted with a descriptive qualitative research which incorporates both qualitative and quantitative instruments to accomplish the objectives of the study. The questionnaires were distributed to the students. The questionnaires had ten close-ended questions. Students were asked to choose one best answer based on their learning experiences or their learning expectations. The results of the study suggest that effective praise and feedback are needed to boost adult leaners’ motivation in learning. Adult learners define characteristics of an effective praise is brief, objective and explicit. Meanwhile, an effective feedback could be delivered in a clear, brief, practical and relevant way. Adult learners also realize the importance of effective praise and feedback to maintain teacher-student interaction which results to positive classroom climate.